Optimization of bio-active compounds from stem of Anisophyllea disticha using supercritical fluid extraction technique - Ferdosh, Sahena; Abdul Bari, Nurul Ashikin; Mia, Abdur Rashid; Sarker, Md. Zaidul Islam (2019)
Background: Anisophyllea disticha is belonging to the species of genus Anisophyllea, is not pharmacologically investigated despite its high utilization by the folklore in treating diarrhea, dysentery, jaundice, revitalizing the birth canal of women, relieving weariness and body aches. Objective: To optimize the total phenolic content (TPC) and antioxidant activities of supercritical fluid extracts of A. disticha in terms of DPPH radical scavenging activities and ferric reducing antioxidant power assay. Material and methods: Stem was chosen and subsequently extracted using supercritical fluid extraction (SFE) and further analyzed. Box-Behnken Design (BBD) was used to optimize and examine the effect of independent variables of SFE such as temperature (50-70˚C), pressure (20-30 MPa) and concentration of co-solvent (10-20%) on TPC and antioxidant activities of A. disticha. Results: The model suggested the optimal conditions of independent variables to be 50˚C, 20 MPa and 17% with predicted TPC of 53.35 mg GAE / g extract, scavenging activity of 96.61% and reducing power of 423.66 mg Fe (II) / g extract. Reverse-phase high performance liquid chromatography (HPLC) was developed for identification and quantification of phenolic compounds (gallic acid, p-coumaric, ferulic acid and quercetin) presented in A. disticha. Run 7 from SFE was chosen as it showed maximum TPC and potent activities and the responses obtained were compared with soxhlet Conclusion: The extract from SFE possessed remarkable TPC, antioxidant activities and concentration of phenolic compounds identified by HPLC, indicating its superior recovery of compounds.